How do you answer this question y=-3x+4 and y=3x-2 with transitive property of equation

Skip to content# How do you answer this question y=-3x+4 and y=3x-2 with transitive property of equation

Mathematics ##
Comments (12) on “How do you answer this question y=-3x+4 and y=3x-2 with transitive property of equation”

### Leave a Reply Cancel reply

How do you answer this question y=-3x+4 and y=3x-2 with transitive property of equation

[tex]-2=-3x+2\ \ \ \ | subtract\ 2\\\\ -4=-3x\ \ \ \ | divide\ by\ -3\\\\ x=\frac{4}{3}[/tex]

Need the graph to answer this.

x = 6/5

Step by step explanation:

2x + 2 = x - 4x + 8

2x + 2 = -3x + 8

2x + 3x = 8 - 2

5x/5 = 6/5

x = 6/5

First copy the problem -3x^2+14x-2

next substitute 2 for x (-3*2) *2 +14(2)-2

then get rid of parentheses -6*2+24-2

then combine like terms member order of operations -12+24-2

and finish it 10

I hope this helped you

This is the answer, hope you understand.

[tex]2x(x++1)(x-2)=a. -x^2 - 7x -2b. -x^2 + 5x +2c. -3x^2 -5x +2d. -3x^2 -5x -2e. -3x^2 +5x -2(i need to[/tex]

Y=-3x+4 and y=3x-2

so -3x+4=3x-2 is also true

-3x+4=3x-2

4=6x-2

6=6x

1=x

-3x^2 -10x -16 -29/(x-2)

Step-by-step explanation:

-3x^3-4x^2+4x+3

We can do synthetic division

-3 -4 4 3

2

Bring the first term down

-3 -4 4 3

2

-3

Multiply -3 times 2

-3 -4 4 3

2 -6

-3

Add -4 and -6

-3 -4 4 3

2 -6

-3 -10

Multiply 2 *-10

-3 -4 4 3

2 -6 -20

-3 -10

Add 4 and -20

-3 -4 4 3

2 -6 -20

-3 -10 -16

Multiply the 2 by -16

-3 -4 4 3

2 -6 -20 -32

-3 -10 -16 -29

The result is -3x^2 -10x -16 -29/(x-2)

2.) 7a^2 + 50a + 7 = 7a^2 + a + 49a + 7 = a(7a + 1) + 7(7a + 1) = (a + 7)(7a + 1)

3.) 3x^2 + 11x - 20 = 3x^2 - 4x + 15x - 20 = x(3x - 4) + 5(3x - 4) = (x + 5)(3x - 4)

4.) x^2 + 7x - 18 = x^2 - 2x + 9x - 18 = x(x - 2) + 9(x - 2) = (x + 9)(x - 2)

Simple...

you have: x=2 --->>> [tex]-3x^{2} +14x-2[/tex]

plug it in-->>>

[tex]-3(2)^{2} +14(2)-2[/tex]

=14

Thus, your answer.

Why is and captilized?

Step-by-step explanation:

if a = 1, and b = 2, then the answer is 47.99999999. if you round that to the nearest whole number, the answer is 48.

[tex]Square root of a^6b times, cube root of a^2b^7[/tex]

(x-2)(-3x^2-10x-16) - 29

Step-by-step explanation:

test -3x^3-4x^2+4x+3 for root at x=2

-3(2)^3-4(2)^2+4(2)+3

=-3*8-4*4+8+3

=-29

so x=2 is not a root n dividing -3x^3-4x^2+4x+3 by x-2 will have a quotient

solving by long division

-3x^3-4x^2+4x+3 x-2

-3x^2

-3x^3+6x^2

-10x^2+4x+3

-10x

-10x^2+20x

-16x+3

-16

-16x+32

-29

so divide -3x^3-4x^2+4x+3 by x-2

= (x-2)(-3x^2-10x-16) - 29